Does It Pay to Graduate from an 'Elite' University in Australia? - David Carroll; Christopher Heaton; Massimiliano Tani (Institute of Labor Economics (IZA), 2018)
In Australia, the so-called Group of Eight (Go8) universities have lower student-to-staff ratios, better qualified staff, superior research outcomes, and generally better placement in university rankings compared to non-Go8 universities. They are also typically the most competitive universities for prospective undergraduates to enter. Prior published research, mainly focusing on the United States, has found that graduates of prestigious and selective colleges enjoy a wage premium over graduates of other institutions when they enter the labour market. In this paper, we use data from the Graduate Destination Survey and data on Australian Tertiary Admission Ranks (ATARs) to investigate the existence of a Go8 premium in the Australian labour market and to determine the extent to which it is due merely to the recruitment of better students. We find statistically significant evidence of unconditional Go8 premia ranging from 4.3% to 5.5% and find that between 13% and 46% of these premia are due to student selection. We also find evidence of considerable heterogeneity within the Go8 and other university groupings, and that field of study and geographical region have relatively large impacts on graduate starting salaries. We conclude that, while Go8 premia exist, a graduate's alma mater is a relatively minor consideration in the determination of graduate salaries in Australia.
Keywords: A23; J24; 330; wage premium; returns to education; human capital; graduate labour market